MANAGEMENT OF INNOVATIVE POTENTIAL OF A COMMERCIAL ORGANIZATION AT DIFFERENT STAGES OF THE LIFE CYCLE OF INNOVATION - L. Ushvitskiy; A. Ter-Grigoryants; O. Belozerova (Вестник Северо-Кавказского федерального университета)
The article discusses the features of the implementation of the innovation life cycle, which determine the different intensity of the involvement of elements of the innovative potential of an economic entity. The content of the individual stages of the innovation life cycle is determined taking into account the influence of external and internal environmental factors, in connection with which the need for a balanced use of enterprise resources is identified. Based on the results of the study, priority areas for the selective use of organizational, administrative, socio-psychological and economic methods for managing the resources of the innovative potential of a commercial structure, focused on increasing the level of efficiency of its use and creating a high-quality and competitive innovative product, were identified.